Geochemistry and origin of heavy oils in the south part of Zhanhua Depression, east China. (May 2019) - Li, Yuyuan; Zha, Ming; Gao, Changhai; Ding, Xiujian; Wang, Xingmou; Zhang, Yunyin; Yang, Liang
Abstract: The Sanhecun sag, located in the south of the Zhanhua depression, has yielded a significant amount of heavy oil in recent years and is becoming a new exploration focus in the Jiyang sub-basin. Surprisingly, oils in the deep Shahejie formation have higher densities and viscosities than those in the shallow Guantao formation. In this study, geochemical and fluid inclusion analyses of oils from different depths were carried out to clarify their source and the cause of the high densities. Oils in the Shahejie formation, with high contents of resins and asphaltenes (47%–56%), are generated from the Es4 carbonate source rocks that were deposited in a hypersaline environment with a relatively high terrigenous organic matter contribution. Maturity parameters and fluid inclusions show that the oils with low saturated hydrocarbon contents and high resin and asphaltene contents were charged to the Shahejie formation from 29 Ma to 27 Ma, when the source rocks were in the early oil generation window. Although subsequent biodegradation further increased oil density, the main control on the high densities of oils in the Shahejie formation is the nature of the source kerogen. Oils in the shallow Guantao formation can be divided into two groups: a group from Es3 source rocks in the Gunan sag and a second from Es3 and Es4 source rocks in the Bonan sag. They were expelled within the oil generation window and charged the reservoirs between 3 Ma and the present-day. Oils in the Guantao formation have undergone light to heavy biodegradation, ranging from PM levels 2 to 5. With the increase of biodegradation level, saturated hydrocarbon contents gradually decrease from 50% to 22%, while the contents of resins and asphaltenes increase from 28% to 43%. Biodegradation is the primary cause of oil densification in the Guantao formation. Although oils in the Guantao Formation suffered more severe biodegradation, they still have higher contents of saturated hydrocarbons than those in the Shahejie Formation. Source type, maturity and biodegradation thus combine, in different ways, to control the density of heavy oils in the Sanhecun sag. This study also indicates that low mature oils from Es4 carbonate source rocks can charge reservoirs in the southern part of Zhanhua depression before late Oligocene uplift, and low mature oil may be a potential future target in this area. Highlights: Geochemical characteristics of heavy oils and fluid inclusion oils described. Origin of heavy oils relate to both source and biodegradation. Low mature oil may be a potential target that was neglected before.